Acid-Sensing Histidine Kinase With a Redox Switch - Inada, Shinya; Okajima, Toshihide; Utsumi, Ryutaro; Eguchi, Yoko (Frontiers in Microbiology, 2021)
The EvgS/EvgA two-component signal transduction system in Escherichia coli is activated under mildly acidic pH conditions. Upon activation, this system induces the expression of a number of genes that confer acid resistance. The EvgS histidine kinase sensor has a large periplasmic domain that is required for perceiving acidic signals. In addition, we have previously proposed that the cytoplasmic linker region of EvgS is also involved in the activation of this sensor. The cytoplasmic linker region resembles a Per-ARNT-Sim (PAS) domain, which is known to act as a molecular sensor that is responsive to chemical and physical stimuli and regulates the activity of diverse effector domains. Our EvgS/EvgA reporter assays revealed that under EvgS-activating mildly acidic pH conditions, EvgS was activated only during aerobic growth conditions, and not during anaerobic growth. Studies using EvgS mutants revealed that C671A and C683A mutations in the cytoplasmic PAS domain activated EvgS even under anaerobic conditions. Furthermore, among the electron carriers of the electron transport chain, ubiquinone was required for EvgS activation. The present study proposes a model of EvgS activation by oxidation and suggests that the cytoplasmic PAS domain serves as an intermediate redox switch for this sensor.